CALCULATION OF CUT AND FILL VOLUMES USING MINING SOFTWARE AT PT BARAMULTI SUKSESSARANA - Yustina Hong Lawing; Wahyu Riadi; Lutpiandi Lutpiandi; Mardi Sutomo (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Cut and fill calculation is an essential stage in open-pit mining activities to determine the volume of soil or rock that must be excavated (cut) and deposited (fill) based on elevation changes between the actual topographic conditions and the planned mine design. This study aims to analyze the results of cut and fill volume calculations using GEOVIA Surpac software in a coal pit area. The data used include topographic maps obtained from RTK (Real Time Kinematic) surveys. The calculation results show a total cut volume of 805.42 MT and a fill volume of 2.09 MT, with a net volume of 803.33 MT, using a rock density of 1. The use of Surpac has proven effective and accurate in calculating material volumes and supporting the optimization of mine design.